A Study of Learning Efficacy Among Rural Area Students in Ledang Johor - Md Sawari, Siti Salwa; Ghazali, Mohd Al'Ikhsan; Mansor, Norwati (2015)
This present study designed to investigate the learning efficacy level among rural area students in Ledang Johor. In additions, this study intends to examine the significant difference level of leaning efficacy between lower and upper form students. Moreover, this study was done to examine the significant difference level of learning efficacy between male and female students. A total of 523 students sampled from four school in Ledang participated in the survey, employing a 12-item questionnaire measuring Learning efficacy. The items were pilot-tested before being administered to the respondents. The data was analysed quantitatively using descriptive statistics, and Independent T-Test. The result shows that, the majority of students experience a moderate level of self-efficacy. Regarding the comparison level of learning efficacy between the lower and upper form students, the finding of the current study indicates that, there is no significant difference level of learning efficacy between lower and upper form students. Lastly, for comparison self-efficacy between male and female, the result revealed there is a significant difference in learning self-efficacy, and female student’s records high score rather than male. This study will provide information regarding secondary students’ level of self-efficacy. Subsequently, counsellors and school administrators can use the information to find appropriate ways to help students increase their self-efficacy level. Hence, students will indirectly benefit from this study. Students can improve their learning performance, be more positive, and focus towards achieving better academic results, which will eventually prevent them from getting involved in any discipline problems.